Palm Morphology and Anatomy - Timothy K. Broschat (EDIS)
Palms differ greatly from broadleaf (dicot) and coniferous (Gymnosperm) trees in their overall form and external structure (morphology) and in their internal structure (anatomy). Morphology and anatomy determine how palms grow, function, and respond to external and internal stress factors. This publication provides a basic understanding of how palms are constructed. This 4-page fact sheet was written by T. K. Broschat, and published by the UF Department of Environmental Horticulture, May 2013.